Transcriptomic and Metabolic Analysis Reveals Genes and Pathways Associated with Flesh Pigmentation in Potato (Solanum tuberosum) Tubers - Man Li; Yuting Xiong; Xueying Yang; Yuliang Gao; Kuihua Li (Current Issues in Molecular Biology)
Anthocyanins, flavonoid pigments, are responsible for the purple and red hues in potato tubers. This study analyzed tubers from four potato cultivars—red RR, purple HJG, yellow QS9, and white JZS8—to elucidate the genetic mechanisms underlying tuber pigmentation. Our transcriptomic analysis identified over 2400 differentially expressed genes between these varieties. Notably, genes within the flavonoid biosynthesis pathway were enriched in HJG and RR compared to the non-pigmented JZS8, correlating with their higher levels of anthocyanin precursors and related substances. Hierarchical clustering revealed inverse expression patterns for the key genes involved in anthocyanin metabolism between pigmented and non-pigmented varieties. Among these, several MYB transcription factors displayed strong co-expression with anthocyanin biosynthetic genes, suggesting a regulatory role. Specifically, the expression of 16 MYB genes was validated using qRT-PCR to be markedly higher in pigmented HJG and RR versus JZS8, suggesting that these MYB genes might be involved in tuber pigmentation. This study comprehensively analyzed the transcriptome of diverse potato cultivars, highlighting specific genes and metabolic pathways involved in tuber pigmentation. These findings provide potential molecular targets for breeding programs focused on enhancing tuber color.